Pengaruh Penerapan Kurikulum Merdeka terhadap Motivasi Belajar Siswa pada Pembelajaran Ekonomi di Sekolah Penggerak SMAN 5 Banjarmasin - Amal, Ikhsanul; Atmono, Dwi; Hasanah, Mahmudah; Nor, Baseran (Jurnal Pendidikan Ekonomi (JUPE), 2024)
This research was conducted to evaluate the effectiveness of implementing the merdeka curriculum designed by the Ministry of Education and Culture in increasing students' learning motivation in economics lessons. This research aims to find out whether the implementation of the independent curriculum has an influence on the economics learning motivation of 12th grade students at SMAN 5 Banjarmasin and how strong the relationship is between these two variables. The method in this research is quantitative descriptive. The subjects in this study were 231 students who chose economics lessons in 12th grade at SMAN 5 Banjarmasin, 70 samples were taken using the Slovin formula. Data analysis uses descriptive analysis, Spearman's Rank Correlation, and simple linear regression tests. The results of this research show that the regression test for the influence of the Merdeka Curriculum on learning motivation can be concluded, namely that there is a significant and positive influence between the application of the Merdeka Curriculum on the economic learning motivation of students at SMAN 5 Banjarmasin and the Spearman's Rank Correlation test shows that the Merdeka Curriculum and Learning Motivation have a positive relationship, with the sufficient or moderate category.